2017
DOI: 10.5021/ad.2017.29.5.602
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Herpes Zoster Recurrence in Central District of Korea

Abstract: BackgroundHerpes zoster is characterized by unilateral grouped vesicles along the distribution of a dermatome. A global recurrence rate as low as 0.5%∼6.2% has been reported for herpes zoster. The recurrence of herpes zoster is higher in immunocompromised patients and older patients.ObjectiveThe purpose of this study is to assess the frequency of herpes zoster recurrence and factors that can influence its recurrence.MethodsFrom January 2005 to December 2015, 14,343 patients with herpes zoster were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The study was relatively large and long-term, surveying 14,343 inpatients and outpatients diagnosed with HZ between January 2005 and December 2015 at six hospitals in South Korea. The study reported that 169 patients experienced recurrence (a recurrence frequency of 1.2%); however, the number of recurrences per patient was not reported [ 15 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was relatively large and long-term, surveying 14,343 inpatients and outpatients diagnosed with HZ between January 2005 and December 2015 at six hospitals in South Korea. The study reported that 169 patients experienced recurrence (a recurrence frequency of 1.2%); however, the number of recurrences per patient was not reported [ 15 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggest that individuals may be exposed to a uniformly increasing cumulative risk of HZ recurrence after the first episode. More studies of this type are required to confirm this hypothesis, both in more varied populations and over longer time periods, given that, when reported, mean time between the first HZ episode and first recurrent HZ episode ranged between 2.0 and 13.7 years [ 11 , 15 , 16 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies have found a lower rate of recurrence within 12 months of the first onset of HZ, and subsequently comparable to the incidence of the first HZ. 5,6 Recurrence of HZ may be associated with immunosenescence. 1 The level of herpes zoster specific cell-mediated immunity (CMI) gradually decreases with age.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent HZ is defined as the appearance of HZ in a patient with a previously infected person with a dermatomal rash and pain. 3 The diagnosis is made clinically in most cases however, the polymerase chain reaction can confirm atypical cases. 4 Treatment of HZ includes optimal and early use of antiviral therapy and analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…2 Recurrent HZ is an uncommon event with a global recurrence rate found varying from as low as 1% to up to 6%. [2][3]6 Treatment for recurrent HZ is similar to that of first episode with antivirals and supportive medications including analgesics.…”
Section: Discussionmentioning
confidence: 99%